Horrid Henry's all time favourite joke book - "Simon, Francesca" (London; Orion Children's Books, 2012)
Laugh your head off with Horrid Henry, his family, friends and enemies as they present more hilarious, ridiculously ribtickling jokes
Donated from "Book Planet", Dated 18-4-2025.
Keywords: Wit and humor